The fearsome dilemma: simultaneous inflation and unemployment - MCLEOD, A.N. (PSL Quarterly Review, 2013)
The work looks at some of the non-monetary (or not specifically monetary) aspects of the problem of simultaneous inflation and unemployment. The author emphasises the domestic considerations and the links between domestic economics and international economics in a general-equilibrium context. Much of the analysis is inevitably couched in terms of money values, but the focus is actually on real output, real income, employment, resource allocation, and other non-monetary objectives. JEL: E32, E24